Motivations for Deciding to Travel Following the Locations of the “Buppesannivas” TV Series - Veerachayluk, Korakot; Phumromsai, Chonlada; Sinpho, Panadda; Chiengkul, Watchara (RMUTI Journal Humanities and Social Sciences, 2025)
This study aims to examine the general characteristics of tourists interested in visiting locations associated with the drama Buppesannivas and to analyze the travel motivations influencing their decision to follow in the footsteps of the drama. The sample consisted of 400 Thai tourists who had watched Buppesannivas. The research instrument was an online questionnaire, and the data were analyzed using descriptive and inferential statistics, specifically multiple regression analysis. The findings indicate that the majority of respondents were female (52.8 %). Most were aged between 19 and 30 years (68.8 %), held a bachelor's degree (55.8 %), and were students (53.5 %). Additionally, 37.8 % had an average monthly income of less than 10,000 THB. The multiple regression analysis using the stepwise method indicates that the aesthetic appeal of the destinations is not a statistically significant factor at the 0.05 level. However, other motivational factors, including personal fulfillment, appreciation of the characters and scenes, the desire to share experiences online, the reputation and popularity of the destinations, and the uniqueness and charm of the locations, significantly influence tourists' decisions to visit locations associated with “Buppesannivas”. These five independent variables collectively explain 62.5 % of the variance in the dependent variable (R² = 0.625), underscoring the importance of these motivations in shaping tourists' travel decisions.